Statistical analysis plan for a pragmatic phase III randomised controlled trial examining behaviour change physiotherapy intervention to increase physical activity following hip and knee replacements: the PEP-TALK trial - Ooms, AG; Dutton, SJ; Parsons, S; Fordham, B; Hing, C; Lamb, SE; Smith, T (BioMed Central, 2021)
Background Total hip (THR) and total knee replacements (TKR) are two highly successful orthopaedic procedures that reduce pain for people with osteoarthritis. Previous evidence suggests that physical activity, at best, remains the same pre- to post-operatively, and in some instances declines. The PEP-TALK trial evaluates the effects of a group-based, behaviour change intervention on physical activity following a THR or TKR.